Effect of Intercropping on Growth and Yield of (Hibiscus sabdariffa L.), Mesta (Roselle) in India - Y. Sandhya Rani; T. Sreelatha; M. Srinivasa Rao; B. Swathi; G. Chitti Babu; S. Mitra (Archives of Current Research International, 2025)
Mesta, scientifically called as Hibiscus sabdariffa (Roselle) is an herbaceous annual plant and lignocellulosic fibre crop is more adaptive under diverse conditions of climate, soil and also resistant to drought. The area under mesta crop is gradually decreasing from the past ten years due to fluctuating price structure, erratic rainfall and introducing crops like maize. Intercropping is one of the most feasible practices under crop diversification and has been a prominent feature for crop production in small holdings in developing countries. Intercropping is promoted among the farmers not only for enhancing farm productivity per unit land but also ensure security against potential risk of monoculture. This can indeed stabilize the diversified needs of the farming households whose production is greatly influenced by vagaries of nature. Considering the importance and possibilities to save the scarce inputs like nutrients, water etc. without reducing the yield and better utilization of land, an investigation was done for three years consecutively at Agricultural Research Station, Amadalavalasa from 2021-2023 during the kharif season to study the feasibility of growing suitable intercrops with mesta on sandy loam soils. The experiment was laid in Randomized Block Design with nine treatments to study the sustainability and profitability of mesta based intercropping system. The data revealed that the mesta + groundnut (3:4) intercropping (33.14 q/ha) recorded the highest mesta fibre equivalent yield followed by mesta + blackgram (3:4). Among the treatments, highest gross returns (Rs. 71134 Rs/ha) was recorded with mesta + groundnut (3:4) treatment with a B:C ratio of 2.59, while the lowest was recorded with mesta + rice (3:4) intercropping system. Hence, keeping in view of the yield and B:C ratio, intercropping system of mesta + groundnut (3:4) followed by mesta + blackgram (3:4) can be suggested as the best alternative cropping pattern to the farmers instead of cultivating a sole mesta crop.